Case Series of Reproductive Outcomes after Surgical Correction of Obstructed Hemivagina in OHVIRA - Megan E. Bunnell; Danielle T. Cipres; Marc R. Laufer (Thieme Medical Publishers, Inc., 2024)
Obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) is a rare congenital developmental syndrome manifested by uterine duplication, lower genital tract obstruction, and unilateral renal anomaly. Literature on reproductive outcomes in this patient population is limited. The aim of this study is to describe obstetric outcomes after surgical correction of obstructed hemivagina in a longitudinal cohort of patients with a diagnosis of OHVIRA. All cases of OHVIRA presenting to a single tertiary care children's hospital from 1990 to 2021 were retrospectively reviewed. Three cases demonstrating a variety of clinically important reproductive outcomes are described in detail including risks such as retained products, endometritis, preterm labor, and malpresentation. Understanding the reproductive outcomes associated with this diagnosis is important for practitioners seeking to counsel and care for patients with this diagnosis. This case series demonstrates a wide array of potential gynecologic and obstetric risks, though ultimately with successful term and near-term pregnancies.